LC-HRMS profiling of phytochemicals, antidiabetic, anticholinergic and antioxidant activities of evaporated ethanol extract of Astragalus brachycalyx Fischer - Kiziltas, Hatice; Bingol, Zeynebe; Goren, Ahmet C.; Pinar, Suleyman Mesut; Alwasel, Saleh H.; Gulcin, Ilhami (Acg Publications, 2021)
Astragalus is a perennial plant that has existed for about 2500-3000 years and consists of more than 250 taxonomic parts. Twenty species of Astragalus are endemic to Turkey, as well as the richest genus with 425 taxa. The roots of Asfragalus species are used in folk medicine as hepatoprotective, antioxidant, antibacterial, antihypertensive, antidiabetic and diuretic. Also, it is used to treat diabetes mellitus, leukemia, nephritis and uterine cancer. It is known that in Anatolia, Astragalus roots are traditionally used against leukemia and wound healing. For the purpose, the measuring of antioxidant activity of evaporated ethanol extract of Asfragalus brachycalyx FISCHER (EEAB), some bioanalytic methods including DPPH center dot and ABTS(center dot+) scavenging effects, ferric ions (Fe3+) and cupric ions (Cu2+) reducing abilities, and metal (Fe') chelating activity were realized. alpha-Tocopherol, ascorbic acid, and BHT were used as the standard antioxidants. On the other hand, some phenolic compounds, which responsible for antioxidant activities of EEAB was determined by liquid chromatography-high resolution mass spectrometry (LC-HRMS). At the similar concentration, EEAB exhibited efficient antioxidant effects when compared to standard compounds. Additionally, EEAB showed IC50 values of 1.985 mu g/mL toward acetylcholinesterase (AChE), 0.620 mu g/mL on alpha-glycosidase and 0.306 mu g/mL against alpha-amylase enzymes.
Keywords: Astragalus brachycalyx; phenolic compounds; antioxidant activity; acetylcholinesterase; alpha-glycosidase; alpha-amylase